Cara Memahami Maqashid Al- Syari’ah - Wijaya, Abdi (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2015)
In completing something that does not have a proposition to establish legal, then maqasid sharia is necessary, because it is wasilah to understand the texts of the Qur’an and the Hadith, in addition, maqsid sharia also aims to meme care of a benefit of mankind and able to provide solutions to the texts contradictory. To understand the maqasid sharia, there is some way to reach them, first; lafaz analysis of these commands and prohibitions and more aimed at issues of worship, the second stage; amr and nahy illah study aimed at social problems of society (muamalah) and a third way; al-sukut ’an syar’iyyah al’ charity.